2017
DOI: 10.1002/nbm.3722
|View full text |Cite
|
Sign up to set email alerts
|

Tensor estimation for double‐pulsed diffusional kurtosis imaging

Abstract: Double-pulsed diffusional kurtosis imaging (DP-DKI) represents the double diffusion encoding (DDE) MRI signal in terms of six-dimensional (6D) diffusion and kurtosis tensors. Here a method for estimating these tensors from experimental data is described. A standard numerical algorithm for tensor estimation from conventional (i.e. single diffusion encoding) diffusional kurtosis imaging (DKI) data is generalized to DP-DKI. This algorithm is based on a weighted least squares (WLS) fit of the signal model to the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…[35] More advanced DKI approach such as double diffusion encoding and symmetrized double pulsed field gradient MRI may provide novel insights of diffusion and kurtosis changes following stroke, which shall be investigated in the future. [47, 48]…”
Section: Discussionmentioning
confidence: 99%
“…[35] More advanced DKI approach such as double diffusion encoding and symmetrized double pulsed field gradient MRI may provide novel insights of diffusion and kurtosis changes following stroke, which shall be investigated in the future. [47, 48]…”
Section: Discussionmentioning
confidence: 99%
“…In studies aiming to address this need, it has been shown that techniques that correlate diffusion over multiple displacements can detect features such as microscopic anisotropy that intra‐voxel averaging may obscure . Briefly, double diffusion encoding (DDE) (also referred to as double pulsed field gradient [double‐PFG]) MRI may yield microstructural information beyond conventional single diffusion encoding MRI . We have developed a symmetrized DDE (s‐DDE, previously referred to as sd‐PFG) NMR sequence that isolates microscopic kurtosis signal from diffusional heterogeneity and demonstrated its use in porous media .…”
Section: Introductionmentioning
confidence: 99%
“…A basic idea behind DP-DKI is that these two 3D vectors can be conveniently concatenated into a single six-dimensional (6D) displacement vector e s s 1 , s 2 ð Þ, where we use a tilde to signify a 6D quantity. 8,11,12,20 The distribution of displacements for the ensemble of diffusion molecules is then fully described by a single 6D probability density function. Associated with this 6D probability density function are a 6D diffusion tensor e D and a 6D kurtosis tensor f W, which are defined in analogy with the usual 3D case that applies to single diffusion encoding.…”
Section: Dp-dkimentioning
confidence: 99%
“…The noise bias correction was based on the standard method proposed by McGibney and Smith 39 and by Miller and Joseph 40 generalized to multiple channel coils, as described in Appendix B. The 6D diffusion and kurtosis tensors were obtained using in house software that implemented the method of Shaw and coworkers, 12 which employs a constrained weighted least squares fitting algorithm similar to ones routinely used for DKI. 41,42 Parametric maps of μFA 0 were then constructed by applying Equations ( 7)- (10).…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation